Synchrotron tomography of magnetoprimed soybean plant root system architecture grown in arsenic-polluted soil - Fatima, Anis; Kataria, Sunita; Jain, Meeta; Prajapati, Rajkumar; Mahawar, Lovely (Frontiers in Plant Science, 2024)
The present study evaluated the repercussions of magnetopriming on the root system architecture of soybean plants subjected to arsenic toxicity using synchrotron source based micro-computed tomography technique for 3D imaging. Seeds of soybean were exposed to the static magnetic field (SMF) strength of (200 mT) for one hour prior to sowing.Magnetoprimed and non-primed seeds were grown-up for one month in a soil-sand mixture containing four different levels of sodium arsenate (0, 5, 10, 50 mg As Kg -1 soil). The results showed that arsenic adversely affects the root growth in non-primed plants by reducing their root length, root biomass, root hair, size and number of root nodules, where the damaging effect of As was observed maximum at higher concentrations (10 and 50 mg As Kg -1 soil).However, a significant improvement in root morphology was detected in magnetoprimed plants where SMF-pretreatment enhanced the root length, root biomass, pore diameter of cortical cells, root hair formation, lateral roots branching, and size of root nodules and girth of primary roots. Qualitative analysis of X-ray micro-CT images showed that arsenic toxicity damaged the epidermal and cortical layers of the root as well as reduced the pore diameter of the cortical cells. However, the diameter of cortical cells pores in magnetoprimed plants was observed higher as compared to plants emerged from non-primed seeds at all concentrations of As toxicity. Thus, the study suggested that magnetopriming has the potential to attenuate the toxic effect of As and could be employed as a pre-sowing treatment to reduce the phytotoxic effects of metal ions in plants by improving root architecture and root tolerance index. This study is the very first exploration of the potential benefits of magnetopriming in mitigating the toxicity of metals (As) in plant roots utilizing the micro-computed tomography technique.